2005
DOI: 10.1111/j.1600-051x.2005.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of superoxide dismutase activity levels in gingiva and gingival crevicular fluid in patients with chronic periodontitis and periodontally healthy controls

Abstract: In CP, SOD activity seems to increase in gingiva, probably as a result of a higher need for SOD activity and protection in gingiva in CP than in periodontal health, while not significantly changing in GCF, suggesting a weak SOD activity in GCF in periodontal disease state. The weak correlation between gingival and GCF SOD activities suggests distinct actions of these SODs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
90
2
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 47 publications
12
90
2
3
Order By: Relevance
“…18) . Although EC-SOD contains Cu and Zn, it is very different from intracellular Cu/Zn-SOD that EC-SOD has much higher relative molecular mass and possess attached carbohydrate 17,19) More recently, ROS have been implicated in the pathogenesis of periodontal disease.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18) . Although EC-SOD contains Cu and Zn, it is very different from intracellular Cu/Zn-SOD that EC-SOD has much higher relative molecular mass and possess attached carbohydrate 17,19) More recently, ROS have been implicated in the pathogenesis of periodontal disease.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Several studies have shown increased generation rate of ROS from peripheral blood polymorphonuclear leukocytes (PMN) in rapidly progressive 17,20) , juvenile 17) , and chronic adult periodontitis 17,21) . There are very few studies concerning the relationship between SOD and inflammation in the oral cavity or periodontium, and the results are conflicting.…”
Section: ⅰ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown increased generation rate of reactive oxygen species from peripheral blood polymorphonuclear leucocytes in rapidly progressive periodontitis, juvenile and chronic adult periodontitis. [3] It is estimated that 1-3 billion reactive species are generated/cell/day, and given this, the importance of the body's antioxidant defense systems to the maintenance of health becomes clear. [4] The body contains a range of enzymatic and nonenzymatic antioxidant systems to protect them against harmful oxidative reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The studies concerning the reactive oxygen species and/or antioxidant mechanisms are also limited in number. [3] The aim of this study was to estimate the superoxide dismutase activity levels in patients with chronic periodontitis (CP) and periodontally healthy controls and with the objectives of to determine the protective anti-oxidant property of superoxide dismutase activity levels in the gingiva in units (U) and in the gingival crevicular fluid (GCF) in units/ml (U/ml) as well as to analyze the correlation between gingival and GCF superoxide dismutase activities levels.…”
Section: Introductionmentioning
confidence: 99%